Microstructural characterization in HEC and EVA modified cement pastes - Silva, Denise Antunes da (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
HEC and EVA polymers are currently used in Brazil for the production of dry-set mortars, which are used for the fitting of ceramic tiles. Despite the widespread application in construction sites, the knowledge about physical or chemical interactions between the polymers, cement and aggregates is poor. The purpose of this paper is to present the results obtained in microstructure characterization tests on HEC and/or EVA modified pastes. Current techniques for characterization of materials were applied, such as differential and gravimetric thermal analysis, X-ray diffraction, Fourier transformed - infrared spectroscopy, and scanning electron microscopy. The effects of polymer type and content, cement hydration time and curing method were evaluated. The results have shown that EVA is the most important factor affecting the microstructure of cement pastes, regardless of the hydration time and curing method, since it physically and chemically interacts with cement, giving rise to the formation of new phases. HEC polymer reduces the effects of EVA polymer, suggesting that some interaction between both polymers can occur in the paste’s aqueous phase.